Tranylcypromine: a promising repurposed drug against Leishmaniases - Oualha, Rafeh; Abdelkrim, Yosser Zina; Essafi-Benkhadir, Khadija; Guizani, Ikram; Harigua-Souiai, Emna (Frontiers in Microbiology, 2026)
Leishmaniases remain a major global health challenge due to limited and often toxic therapeutic options. Recent advances in artificial intelligence have enabled the identification of novel antileishmanial candidates through drug repurposing approaches. Among these, our team has previously predicted in silico the monoamine oxidase inhibitor Tranylcypromine as a potential drug candidate against Leishmaniases. In this study, we provided the first experimental evidence supporting its efficacy against Leishmania major using both promastigote and intracellular amastigote models. Tranylcypromine markedly decreased parasite viability in a concentration-dependent manner, displaying IC50 values of 83.6 and 31.6 μg/ml against promastigotes and amastigotes, respectively. Mechanistic investigations revealed that at concentrations ranging from 50 to 200 μg/ml, it induced an apoptotic death of L. major promastigotes leading to necrosis at higher concentrations. Viability and cytotoxicity assays on THP-1-derived macrophages highlighted that the compound, at the selected concentrations, was safe and did not induce a toxic effect on host cells with CC50 values exceeding 280 μg/ml. Altogether, these findings revealed Tranylcypromine as a selective and promising antileishmanial drug candidate, supporting the relevance of AI-assisted drug repurposing strategies to accelerate drug discovery of safe and affordable therapies for neglected tropical diseases.